Konsep Pembentukan Karakter Siswa Madrasah Aliyah Menurut Abdul Malik Fadjar: Pendekatan Pendidikan untuk Membangun Karakter yang Kuat - M. Mualif, M. Mualif (Pusat Riset dan Inovasi Nasional, 2025)
Character education has become a central discourse in improving the quality of human resources in Indonesia, especially considering the moral issues faced by the younger generation, ranging from low integrity to substance abuse. These issues indicate that the current educational approach is still suboptimal in shaping students' character. This study aims to examine the concept of character development for students in Madrasah Aliyah according to Abdul Malik Fadjar, placing his ideas within the framework of Islamic teachings and contemporary education theory. The research method used is library study and content analysis, with primary sources including Fadjar's writings, national policies, and research by experts such as Lickona, Habermas, and al-Ghazali. The analysis shows that Fadjar views character education as a strategic investment that should be integrated into all aspects of the curriculum and school culture. His concept involves integrating divine dimensions (faith, excellence, piety) and human dimensions (brotherhood, justice, tolerance) into the educational process. The main pedagogical strategies he offers include exemplary behavior (uswah hasanah), habituation of values (pembiasaan), and guidance/advice (dakwah/nasihat). This approach is implemented through planned routines, extracurricular activities, and the integration of religious knowledge with general knowledge. The implementation of Fadjar’s concept in the Diniyah program and the Integrated Education System (SPT) in Aceh proves the effectiveness of this model in developing students who are intelligent, virtuous, and globally competitive. This research recommends the development of longitudinal character evaluation instruments, intensive teacher training, and empirical field studies to measure the long-term impact of Fadjar's strategy on students' moral attitudes and academic achievements. Thus, character education according to Fadjar can serve as a relevant model in addressing the challenges of education and morality in Indonesia today.